2003
DOI: 10.1016/s1567-1356(02)00134-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of yeast species from orange fruit and juice by RFLP and sequence analysis of the 5.8S rRNA gene and the two internal transcribed spacers

Abstract: Yeast isolates from orange fruit and juice in a spontaneous fermentation were identified and classified by two molecular techniques. The first was analysis of the restriction pattern generated from the polymerase chain reaction (PCR)-amplified 5.8S rRNA gene and the two internal transcribed spacers (ITS) using specific primers. The second technique was sequence analysis of the ITS regions using the same two primers. Nine different restriction profiles were obtained from the size of the PCR products and the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…Sequence analysis of the ITS-5.8S region or the D1/D2 domains in the large 26S subunit of rDNA are also used in identification tests (Baleiras Couto et al 2005;Martorell et al 2006). These molecular techniques are useful for rapid identification of yeasts in wine ecosystems (Capece et al 2003;Sun et al 2009) and also in other foods (Heras-Vazquez et al 2003;Rómo-Sánchez et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Sequence analysis of the ITS-5.8S region or the D1/D2 domains in the large 26S subunit of rDNA are also used in identification tests (Baleiras Couto et al 2005;Martorell et al 2006). These molecular techniques are useful for rapid identification of yeasts in wine ecosystems (Capece et al 2003;Sun et al 2009) and also in other foods (Heras-Vazquez et al 2003;Rómo-Sánchez et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This rDNA region is sufficiently variable to allow reliable identification of yeast species. More recently, the differences in the rRNA internal transcribed spacer (ITS) have been used to identify yeast species (Las Heras-Vazquez et al 2003). The ITS region is relatively short (500-800 bp) and can be easily amplified by PCR using universal single primer pairs that are complementary to conserved regions within the rRNA subunit genes (White et al 1990), and the ITS region may be highly variable among morphologically distinct species and so ITS-generated RFLP restriction data can be used to estimate genetic distances and provide characters for systematic and phylogenetic analysis (Bridge et al 1998;Petersen et al 2001;Arias et al 2002;Alvarez-Martin et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…unisporus has been previously characterized in kefir (Marquina et al 2002) and has also been found in naturally fermented fruit juices (Las Heras-Vazquez et al 2003). S. humaticus is a recently described species (Mikata et al 2001).…”
Section: Resultsmentioning
confidence: 99%